Prenatal cocaine exposure and child outcomes: a conference report based on a prospective study from Cleveland. (July 2015) - Singer, Lynn T.; Minnes, Sonia; Min, Meeyoung O.; Lewis, Barbara A.; Short, Elizabeth J.
<x xml:space="preserve">Abstract</x> Objective The study aims to describe developmental outcomes from a longitudinal prospective cohort (Cleveland study) of prenatally cocaine‐exposed (CE) infants. Methods Two hundred eighteen CE and 197 nonexposed infants were enrolled at birth and followed through mid‐adolescence. Birth CE status was determined by interview and biologic measures. Multiple demographic, drug, and environmental correlates were controlled. Standardized, normative, reliable measures of fetal growth, intelligence quotient (IQ), behavior, executive function, and language were given at each age and risk for substance misuse assessed in adolescence. A subset of children received volumetric magnetic resonance imaging (MRI) at 7 years and functional MRI at 14 years. The effect of CE was determined through multiple regression analyses controlling for confounders. Results Cocaine exposed had significant negative effects on fetal growth, attention, executive function, language, and behavior, while overall IQ was not affected. CE had significant negative effects on perceptual reasoning IQ and visual–motor skills and predicted lower volume of corpus callosum and decreased gray matter in the occipital and parietal lobes. CE children had higher risk for substance misuse. Confounding risk factors had additive effects on developmental outcomes. Conclusions Prenatal exposure to cocaine was related to poorer perceptual organization IQ, visual–spatial information processing, attention, language, executive function, and behavior regulation through early adolescence. Copyright © 2015 John Wiley & Sons, Ltd.